Respuesta :

Answer:

The answer would be 2 +/- √-2

Step-by-step explanation:

In order to complete the square, we have to start by getting all of the constants to the right side.

k^2 - 4k + 1 = -5

k^2 - 4k = -6

Now we need to take the k coefficient (-4) and cut it in half (-2). Now we square that number (4) and add it to both sides

k^2 - 4k + 4 = -6 + 4

k^2 - 4k + 4 = -2

Now we can factor the left side and solve.

(k - 2)^2 = -2 ----> take the square root of both sides

k - 2 = +/- √-2

k = 2 +/- √-2

ACCESS MORE